2007
DOI: 10.1190/1.2785978
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh-to-shear wave conversion at the tunnel face — From 3D-FD modeling to ahead-of-drill exploration

Abstract: For safe tunnel excavation, it is important to predict lithologic and structural heterogeneities ahead of construction. Conventional tunnel seismic prediction systems utilize body waves ͑P-and S-waves͒ that are directly generated at the tunnel walls or near the cutter head of the tunnel boring machine ͑TBM͒. We propose a new prediction strategy that has been discovered by 3D elastic finite-difference ͑FD͒ modeling: Rayleigh waves arriving at the front face of the tunnel are converted into high-amplitude S-wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 20 publications
(6 reference statements)
3
25
0
1
Order By: Relevance
“…In addition to the calculated distances (the tunnel face positions plus the offsets), we also plotted the determined formation S-wave velocity. The distance between the tunnel face and the Piora basin is stable at about 50 m for each window, and corresponds very well with both the rock quality index (RQD, Figure 4b) and imaging results from a previous publication (Bohlen et al, 2007). Also, the formation S-wave velocities of about 3100 m/s obtained from each processing loop agree with results from previous surveys (Borm et al, 2003).…”
Section: Field Data Observationssupporting
confidence: 81%
See 3 more Smart Citations
“…In addition to the calculated distances (the tunnel face positions plus the offsets), we also plotted the determined formation S-wave velocity. The distance between the tunnel face and the Piora basin is stable at about 50 m for each window, and corresponds very well with both the rock quality index (RQD, Figure 4b) and imaging results from a previous publication (Bohlen et al, 2007). Also, the formation S-wave velocities of about 3100 m/s obtained from each processing loop agree with results from previous surveys (Borm et al, 2003).…”
Section: Field Data Observationssupporting
confidence: 81%
“…Also, the formation S-wave velocities of about 3100 m/s obtained from each processing loop agree with results from previous surveys (Borm et al, 2003). Bohlen et al,2007).…”
Section: Field Data Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical simulations of a tunnel seismic experiment using the method of finite-difference modelling [9] showed that only little P-wave energy is gererated and most of it is directed sidewards to the tunnel. P-waves are therefore of limited use for looking ahead when they are not generated at the tunnel face or away from the tunnel wall.…”
Section: Introductionmentioning
confidence: 99%